Fiber reinforced silicon-containing arylacetylene resin composites (eXPRESS Polymer Letters)
A silicon-containing arylacetylene resin (SAR), a poly(dimethylsilyleneethynylene phenyleneethynylene) (PMSEPE), was synthesized. The PMSEPE is a solid resin at ambient temperature with a softening temperature about 60°C and soluble in some solvents like tetrahydrofuran. The melt viscosity of the PMSEPE resin is less than 1 Pa•s. The resin could cure at the temperature of lower than 200°C. Fiber reinforced PMSEPE composites were prepared from prepregs which were made by the impregnation of fibers in PMSEPE resin solution. The composites exhibit good mechanical properties at room temperature and 250°C. The observation on fracture surfaces of the composites reinforced by glass fibers and carbon fibers demonstrates that the adhesion between the fibers and resin is good. The results from an oxyacetylene flame test show that the composites have good ablation performance and XRD analyses indicate that SiC forms in the residues during the ablation of the composites.